Træl – Tralle – Trælleborg - Lunn, Nils (Kuml, 1957)
Træl - Tralle - Trælleborg The origin of the name Trælleborg has been variously sought in the words Træl - a slave, Trælle - to perform forced labour, Træl - a supporting post, and Tralle - an open palisade or collonnade. The widespread occurrence of the name shows it to have been a type-name. That forts of the strategic importance of the "trælleborgs" could have been occupied by slaves may be disregarded; and that they were built by slaves would only have been worthy of permanent record if this were an unusual occurrence. However, as they are fortifications of such size or positional importance that they can hardly have been private ventures, it is possible that the king or his constable requisitioned labour for their building and thereby gave rise to the name. lf the name is rather to be derived from Træl - a supporting post or Tralle - an open palisade, then we may expect that the external appearance of these borgs would bear some conspicuous feature to suggest the name. At the original Trælleborg near Slagelse there were traces of a lower fighting-platform on the outer side of the rampart about 1-2 meters above its foot. The breastwork protecting this was of planks strengthened by oblique supporting posts, set in the berm about 1 meter from the foot of the rampart and about a foot's breadth apart. It would have been a conspicuous feature and would conform to what we understand by a Tralværk. The palisade on the summit of the rampart has left no traces capable of interpretation but, remembering that the armament of the period consisted of bows, javelins, slings, spears, axes and swords, with no heavy artillery such as catapults, it is not impossible that this palisade consisted of a row of massive posts higher than a man and a little under shoulder-breadth apart, joined together at breast height and below with a heavy wickerwork screen. This would give the necessary protection against storming while still allowing free use of weapons, and it would in appearance have resembled a Tralværk. Niels Lunn